2021
DOI: 10.1021/acsami.1c07366
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable and Multi-Metal–Organic Framework Fabrics Via High-Yield Rapid Sorption-Vapor Synthesis and Their Application in Chemical Warfare Agent Hydrolysis

Abstract: Protocols to create metal−organic framework (MOF)/polymer composites for separation, chemical capture, and catalytic applications currently rely on relatively slow solution-based processing to form single MOF composites. Here, we report a rapid, high-yield sorption-vapor method for direct simultaneous growth of single and multiple MOF materials onto untreated flexible and stretchable polymer fibers and films. The synthesis utilizes favorable reactant absorption into polymers coupled with rapid vapor-driven MOF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…Previously, using DMF-based solvents, polyamide@UiO-66-NH 2 fabrics formed by vapor-sorption synthesis showed that the extent of MOF loading changed in proportion to the concentration of MOF precursors in the starting solution . Therefore, the results in Figure suggest that any resulting changes in the concentration of the precursor solution do not significantly influence the MOF growth.…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…Previously, using DMF-based solvents, polyamide@UiO-66-NH 2 fabrics formed by vapor-sorption synthesis showed that the extent of MOF loading changed in proportion to the concentration of MOF precursors in the starting solution . Therefore, the results in Figure suggest that any resulting changes in the concentration of the precursor solution do not significantly influence the MOF growth.…”
Section: Resultsmentioning
confidence: 85%
“…As presented in Scheme , MOF-fabrics were synthesized by submerging fabric swatches in a precursor solution to absorb MOF precursors, followed by suspending the damp samples above a heated modulator solution. The modulator vapor then promoted MOF reactants to diffuse from the fabric and form well-adhered crystalline MOFs on the surface of each fiber . The precursor solutions used the same solvent compositions as for the powder synthesis (Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations